Optimalisasi Pembelajaran Melalui Pelatihan Pembuatan Media Classpoint bagi Guru Sekolah Dasar - Indraswati, Dyah; Sobri, Muhammad; Rahmatih, Aisa Nikmah; Asri Fauzi; Lalu Wira Zain Amrullah (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2024)
This community service aims to provide guidance to teachers to optimize learning by creating learning media through the Classpoint application. The implementation of this community service activity is done face-to-face (offline), while adhering to applicable health protocols. The method of implementing community service includes problem identification, presentation by the team of lecturers, question and answer sessions and discussions, as well as direct assistance in the process of making interactive Classpoint media. The media developed through the Classpoint application is expected to motivate students to learn and increase their participation in building knowledge. Training at State Elementary School 14 Cakranegara went smoothly with the assistance of 5 members of the community service team and 2 students who guided 10 participants, thus enabling them to overcome obstacles quickly. The speakers were also highly communicative, providing step-by-step guidance, and ensuring that each participant understood the steps before moving on to the next stage. During the training, the five types of Classpoint application features, such as multiple choice, word cloud, short answer, slide description, and image upload, could be effectively applied.